Immunoglobulin-binding activity among pathogenic and carrier isolates of Haemophilus somnus. - Widders, P R (1989)
Nonimmune binding of immunoglobulin to whole bacteria was quantitated for North American isolates of Haemophilus somnus recovered from cattle with pneumonia, reproductive failure (abortion), or thromboembolic meningoencephalitis or from the vagina or prepuce of carrier cattle. Quantitative binding activity covered a wide range, with most pathogenic and carrier isolates demonstrating significant immunoglobulin-Fc binding. Isolates for which Fc binding was not detectable were recovered only from the prepuces of asymptomatic bulls. Expression of Fc-binding activity correlated with the presence of the 41,000-molecular-weight protein (41K protein) and 270K protein. Isolates that lacked Fc-binding activity did not possess 41K or 270K protein. A 33K protein was detected in isolates that lacked Fc-binding activity but not in isolates that bound Fc.